A study of self medication among the adult people of the Nanded city, western India - Gadekar, Rambhau Dhondibarao; Gattani, Prakash Laxminarayan; Dhande, Vishal Samadhan (International Journal Of Community Medicine And Public Health, 2017)
Background: Modern medicines are of prime importance to human being and are potentially hazardous when taken indiscriminately in the form of self medication. The main objective was to study the practice of self medication and the common ailments, drugs used, sources of information and the reasons for it. Methods: A community based cross sectional study was carried out on 300 urban adults. From the four zone of Nanded city, one zone was selected by lottery method and from that zone one pharmacy (medical) shop was selected randomly for data collection. Adult people who bought medicines from the selected shop without any prescription were interviewed for information regarding sociodemographic factors like age, sex, residence, education, occupation etc and information about over the counter drug such as which drug they purchased, what was the main symptom of their illness, reasons for not consulting doctor, sources of information about over the counter drug etc. were collected on predesigned and pretested semi structured proforma. Results: Out of 300 study subjects 78.3% were males and 21.7% were females. Maximum study subjects, 39.0% were from 30-39 years of age group and 23% study subjects were educated up to secondary school level. Most common symptom was fever (21%) followed by headache (15%). The commonest category of drug used for self medication was analgesic drugs (27%) and majority of study subjects said pharmacist was the main source of information about OTC drugs (48.7%). 45% study subject stated that reason for self medication was high consultation fees of private doctors. Conclusions: Active age group male members in the family were more involved in self medication and high consultation fees of private doctors was the main reason for not consulting the doctor and practicing self medication.